1965
DOI: 10.1002/jcp.1030650215
|View full text |Cite
|
Sign up to set email alerts
|

Limiting factors involved in CO2 production by starved and X‐irradiated starved yeast cells

Abstract: Studies of reduced COZ production by starved yeast cells were carried out to localize the site limiting this process and responsible for a greater production by irradiated cells. Cell-free extracts prepared before and after starvation of cells, and from irradiated and unirradiated cells, showed similar hexokinase activity and produced similar amounts of COz. These results demonstrated that rate limiting glycolytic enzymes did not decay during starvation, were not induced during a lag period i n COz production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1965
1965
1971
1971

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Organism and hiandlintg. Yeast cells (Saccharomyces cerevisiae) were grown as described previously (10), except that temperature was adjusted to 28.5 C. For most measurements, the cells were harvested during exponential growth at a count of 2 X 107/ml and washed twice by centrifugation with distilled water before experimental use (11).…”
Section: Methodsmentioning
confidence: 99%
“…Organism and hiandlintg. Yeast cells (Saccharomyces cerevisiae) were grown as described previously (10), except that temperature was adjusted to 28.5 C. For most measurements, the cells were harvested during exponential growth at a count of 2 X 107/ml and washed twice by centrifugation with distilled water before experimental use (11).…”
Section: Methodsmentioning
confidence: 99%
“…The data in the last column of Table V show that the capacities of cell extracts to produce C 0 2 from glucose were similar, except where a marked decrease in the capacity to decarboxylate pyruvate was found. Previous measurements showed that rates of C 0 2 output by extracts of starved and unstarved cells also are similar (15). Incubation in solutions of readily used sugars at high concentrations (0.1 M glucose or 0.2 M maltose) reduced the capacity to decarboxylate pyruvate, whereas other compounds did not affect this capacity or increased it.…”
Section: Metabolite Lossesmentioning
confidence: 82%
“…Elimination of the lag by ethyl but not by methyl alcohol, however, is consistent with an effect unrelated to a metabolic use (additions of 0.1 M ethyl alcohol, but not 0.1 M methyl alcohol, also removed the lag from cells incubated in 0.2 M lactose and in 0.2 M sorbose). Thus, removal of the lag period may be interpreted as an alteration in intracellular membrane restrictions so that required intermediates, or glucose which enters the cell immediately (15), are able to move to appropriate cellular sites. The components necessary for C 0 2 production evidently were present within starved cells; they simply needed to be brought together.…”
Section: Metabolite Lossesmentioning
confidence: 99%